Estimation of the hepcidin level and some Biochemical parameters in patients of polycystic ovary Syndrome in Kirkuk city - Sherin Bahgat Ayed AL- Tikriti; Nazar Ahmed Naji (Tikrit Journal of Pure Science)
Polycystic ovary Syndrome is a common disorder in the endocrine glands, which is characterized by the aggregation of small bags surrounded by theca internal layers bloated follicles .